Economic Intelligence in Support of Diversification: what Effects Characterize the Pharmaceutical Industry? - Meroudj, Mohamed Ali; Kerkoub, Azzedine Ibrahim (Finance and Business Economies Review, 2023)
Nowadays, information has become a critical value-added resource for all companies that want to maintain their stability and sustainability for as long as possible, because the environment in which they evaluate is increasingly characterized by a constantly increasing and intensifying complexity and competitiveness. As a result, companies must explore innovative techniques for gathering relevant information; that facilitates their management while also enabling them to support and implement their strategic orientations. The current study intends to investigate the relationships between two crucial concepts for contemporary companies: economic intelligence as a strategy for information acquisition and diversification as an approach to strategic planning. As an empirical field, we performed our research using industrial companies in the Algerian pharmaceutical sector. The findings indicate the presence of effects between the adoption of diversification and economic intelligence practices.